ANALYSIS OF MICROPLASTIC CONTENT IN LOKAN (Geloina erosa) IN NORTH BEACH WATERS OF BENGKALIS ISLAND, RIAU PROVINCE - Sari, Nian; Amin, Bintal; Yoswaty, Dessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
The coastal waters of Pulau Bengkalis are located in the Malacca Strait and it is suspected that some of the people around the area throw away garbage and end up at sea, especially plastic waste. This research was conducted in July 2020 in the northern coastal waters of Bengkalis Island, Bengkalis Regency. The aim of this study was to analyze the type, abundance and relationship of abundance with microplastic size in Lokan soft tissue. This study uses a survey method. Data collection is primary data, data obtained during the study is presented in tables and graphs, then analyzed statistically. The results showed 3 types of microplastics, namely fibre, film and fragments. The total abundance of microplastics at station 1 was 13.199 particles/g and the total abundance at station 2 was 13.583 particles / g. The total abundance of microplastics at the large size was 8.942 particles/g and the total abundance was higher at the small size, namely 15.774 particles/g. The results of the regression test showed that the abundance of microplastics had a weak relationship with the weight and length of the fish with a correlation coefficient between 0.21-0.40.